Review: roles of mycorrhizal symbioses and associated soil microbiomes in ecological restoration - Lethielleux-Juge, Christine (Frontiers in Microbiology, 2025)
The ecological roles of Arbuscular Mycorrhizal Fungi (AMF) are diverse, providing essential nutrients to host plants, tolerance to stress, and regulation of metabolic pathways, greatly involved in soil C dynamics, unlocking minerals and promoting reactive Fe minerals. Although spores dispersal modes are still not clearly understood, a strong positive relationship exists between intra-and extraradical mycelium at the ecosystem level. AMF are essential in ecosystem restoration by improving soil attributes, above and belowground biodiversity, seedlings survival, growth, and establishment on stressed soils, driving plant succession and preventing plant invasion. AMF inoculants from native and early seral instead of exotics and late seral, consortia instead of few or single species, are more efficient. Plant and AMF communities evolve together after revegetation, fine fescues are among the most resilient species, especially Festuca rubra, whose fungal strategies have been recently finely studied. Distinct AMF communities are associated with functionally different plants, which are related to differences in P and C transportomes and genetic variations within the AMF symbiont. Ligneous species react differently to forest soil inoculations according to their arbuscular mycorrhizal symbiosis (AM) or ectomycorrhizal symbiosis (EM) status, and in dual-mycorrhizal plants, costs and benefits are context-dependent, with mycorrhizal switch occurring under various abiotic or biotic factors and resource availability. In mine restoration, root colonization is generally very low during the first year post-reclamation, then increases rapidly before stabilizing. Parallel to plant successions, increased soil parameters, and decreased contaminants, AMF diversity increased and changed, affiliated Glomus genera with small spores being completed by Acaulospora or Gigaspora larger spores under southern climates. A similar recovery period was observed for fungal communities in forest restoration, where ectomycorrhizal mycorrhizal fungi (EMF) species dominate, and diversity increased with time post-revegetation, influenced by edaphic variables and tree species. Under heavy metal (HM) contamination, microorganism classes, enzymes, and AMF efficiency vary with time, soil parameters, restoration treatments, plant species, and levels of soil contamination, with Proteobacteria and Actinobacteria being often predominant. Dual applications of specific microbial and AMF species induced synergistic effects on plant growth and soil resilience. Under other contaminants, several AMF and microbial consortia proved to favorize plant growth and nutrient availability and decrease soil toxicity. New quality indicators to compare rehabilitation studies are proposed.